Between Bulgaria, Byzantium and Serbia – the monastic pilgrimages of St. Theodosius of Tarnovo and St. Romil of Vidin - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2009)
The article analyses the activities of two representatives of late medieval Balkan monasticism: St. Theodosius of Tarnovo and St. Romyl of Vidin. The starting point is the political and religious context of the 14th century. The author presents the spiritual journeys of both monks, which reflect the existence of the supranational community of the Orthodox Church and the development of the mystical-ascetic movement (hesychasm) in Eastern Christianity. The author presents the spiritual journeys of both monks, whose fates document the existence of a supranational community of the Orthodox Church and the development of a mystical-ascetic movement (hesychasm) in Eastern Christianity. The aim is to highlight the common elements of the spiritual path of both monks in the context of their travels between the monastic centres of the Balkans and Byzantium. The source of the research are two biographies: that of Theodosius by the Patriarch of Constantinople, Callistus, and that of Romil, written by his disciple, Gregory Dobropis. Both texts are compared with Byzantine and Bulgarian literature, which allows for the establishment of a relative chronology of the migrations. The conclusions indicate that they were motivated both by the search for spiritual masters and by the need to escape political and military threats. The author also emphasises the importance of both monks for the spread of Hesychasm in the Orthodox tradition, symbolised by the monastery of Theodosius in Kilifarevo and Romil's hermitic asceticism. Despite their different experiences, both monks contributed to the spiritual integration of the Balkans and the consolidation of the Orthodox community across national borders.